Manufacturing method of electromagnetic wave shielding sheet, and electromagnetic wave shielding sheet

By incorporating inorganic pigments with an aspect ratio of 10 or more into a dispersion with carbon nanotubes and carboxymethylcellulose sodium, the method addresses the cost issue of using carbon nanotubes, achieving high electromagnetic shielding properties at a lower cost.

JP7669117B2Active Publication Date: 2025-04-28HOKUETSU CORP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2020065639
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-04-01
Publication Date
2025-04-28
Estimated Expiration
2040-04-01

AI Technical Summary

Technical Problem

Carbon nanotubes are expensive compared to inorganic pigments, making it challenging to manufacture an electromagnetic shield sheet with high shielding properties at a low cost.

Method used

A method involving the use of carbon nanotubes, inorganic pigments such as kaolin, mica, or talc, and carboxymethylcellulose sodium, where the aspect ratio of the inorganic pigment is 10 or more, to create a dispersion that is then dried to produce an electromagnetic shield sheet with enhanced shielding properties.

Benefits of technology

The method achieves high electromagnetic shielding properties while reducing production costs by partially replacing carbon nanotubes with inorganic pigments, resulting in a cost-effective electromagnetic shield sheet.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007669117000001
    Figure 0007669117000001
  • Figure 0007669117000002
    Figure 0007669117000002
  • Figure 0007669117000003
    Figure 0007669117000003
Patent Text Reader

Abstract

To provide a production method of an electromagnetic wave shield sheet that produces an inexpensive electromagnetic wave shield sheet having high shield performance against an electromagnetic wave.SOLUTION: A production method of an electromagnetic wave shield sheet related to the invention includes a step for preparing a dispersion liquid containing a carbon nanotube, inorganic pigment, carboxymethyl cellulose, and water and a step for drying the dispersion liquid. The inorganic pigment has an aspect ratio of 10 or higher.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to a method for manufacturing an electromagnetic wave shielding sheet, and an electromagnetic wave shielding sheet. [Background technology]

[0002] Carbon nanotubes have a structure similar to a uniform, flat piece of graphite rolled up into a cylinder. Both ends of a carbon nanotube are closed with a structure similar to the hemispheres of fullerenes, and each end always contains six five-membered rings. Due to this unique structure, carbon nanotubes have a variety of properties, and are expected to be applied in a wide range of fields.

[0003] For example, Patent Document 1 describes the production of a sheet for shielding electromagnetic waves from an aqueous dispersion of carbon nanotubes using a polysaccharide such as carboxymethyl cellulose and an anionic surfactant as dispersants. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Japanese Patent Application Laid-Open No. 2013-82610 Summary of the Invention [Problem to be solved by the invention]

[0005] Carbon nanotubes as described above are more expensive than inorganic pigments, so if it were possible to replace some of the carbon nanotubes with inorganic pigments while still maintaining electromagnetic wave shielding properties, it would be possible to produce a low-cost electromagnetic wave shielding sheet.

[0006] An object of some aspects of the present invention is to provide a method for producing an electromagnetic wave shielding sheet that has high electromagnetic wave shielding properties and is inexpensive.An object of some aspects of the present invention is to provide an electromagnetic wave shielding sheet that has high electromagnetic wave shielding properties and is inexpensive. [Means for solving the problem]

[0007] One aspect of the method for producing an electromagnetic wave shielding sheet according to the present invention is to Carbon nanotubes, inorganic pigments, and carboxymethyl cellulose sodium and water; drying the dispersion; Including, The inorganic pigment has an aspect ratio of 10 or more.

[0008] In one embodiment of the method for producing an electromagnetic wave shielding sheet, The inorganic pigment may be at least one selected from the group consisting of kaolin, mica, and talc.

[0009] In any one of the above-described methods for producing an electromagnetic wave shielding sheet, The inorganic pigment may be kaolin.

[0010] In any one of the above-described methods for producing an electromagnetic wave shielding sheet, In the dispersion, the ratio of the mass of the inorganic pigment to the mass of the carbon nanotubes may be 1 / 4 or more and 1 or less.

[0011] In any one of the above-described methods for producing an electromagnetic wave shielding sheet, In the dispersion, the ratio of the carboxymethyl cellulose to the total mass of the carbon nanotubes and the inorganic pigment is sodium The ratio of the masses may be 3 or less.

[0012] In any one of the above-described methods for producing an electromagnetic wave shielding sheet, In the step of preparing the dispersion, the carboxymethyl cellulose is used as a dispersant. sodium Only may be used.

[0013] In any one of the above-described methods for producing an electromagnetic wave shielding sheet, The step of preparing the dispersion includes: The carbon nanotubes and the carboxymethyl cellulose sodium and water to prepare a mixed solution; dispersing the carbon nanotubes contained in the mixture by an underwater head-on collision method; may include:

[0014] One aspect of the electromagnetic wave shielding sheet according to the present invention is Carbon nanotubes, inorganic pigments, and carboxymethyl cellulose sodium and, The inorganic pigment has an aspect ratio of 10 or more.

[0015] In one embodiment of the electromagnetic wave shielding sheet, The inorganic pigment may be at least one selected from the group consisting of kaolin, mica, and talc.

[0016] In any one of the above-mentioned electromagnetic wave shielding sheets, The inorganic pigment may be kaolin.

[0017] In any one of the above-mentioned electromagnetic wave shielding sheets, The ratio of the mass of the inorganic pigment to the mass of the carbon nanotubes may be 1 / 4 or more and 1 or less.

[0018] In any one of the above-mentioned electromagnetic wave shielding sheets, the carboxymethyl cellulose relative to the total mass of the carbon nanotubes and the inorganic pigment sodiumThe ratio of the masses may be 3 or less. [Effects of the Invention]

[0019] According to the method for producing an electromagnetic wave shielding sheet of the present invention, it is possible to produce an electromagnetic wave shielding sheet that has high shielding properties against electromagnetic waves and is low cost. Furthermore, the electromagnetic wave shielding sheet of the present invention can have high shielding properties against electromagnetic waves and is low cost. [Brief explanation of the drawings]

[0020] [Figure 1] 3 is a flowchart illustrating a method for manufacturing an electromagnetic wave shielding sheet according to the present embodiment. [Figure 2] 1 is a table for explaining inorganic pigments used in the experimental examples. [Figure 3] 1 is a table showing the evaluation results of the electromagnetic wave shielding properties of coated paper. [Figure 4] 1 is a table showing the evaluation results of the electromagnetic wave shielding properties of the dry film. [Figure 5] 1 is a table showing the evaluation results of dispersibility of dispersions 1 to 12. [Figure 6] Photographs showing the state of dispersions 1 to 12 after drying overnight. [Figure 7] 1 is a table showing the evaluation results of the electromagnetic wave shielding property when the ratio of carbon nanotubes to sodium carboxymethyl cellulose is changed. [Figure 8] A graph showing "S21" versus frequency. [Figure 9] A graph showing "S21" versus frequency. [Figure 10] 10 is a table showing the evaluation results of electromagnetic wave shielding properties when the number of passes is changed. [Figure 11] A graph showing "S21" versus frequency. [Figure 12] A graph showing "S21" versus frequency. DETAILED DESCRIPTION OF THE INVENTION

[0021] Preferred embodiments of the present invention will be described in detail below with reference to the drawings. Note that the embodiments described below do not unduly limit the content of the present invention as defined in the claims. Furthermore, not all of the configurations described below are necessarily essential components of the present invention.

[0022] 1. Manufacturing method of electromagnetic wave shielding sheet First, a method for manufacturing an electromagnetic wave shielding sheet according to this embodiment will be described with reference to the drawings. Fig. 1 is a flowchart for explaining the method for manufacturing an electromagnetic wave shielding sheet according to this embodiment.

[0023] The method for producing the electromagnetic wave shielding sheet according to this embodiment is a method for producing a composite material containing carbon nanotubes (hereinafter also referred to as "CNTs"), an inorganic pigment, and carboxymethyl cellulose. sodium The method for producing an electromagnetic wave shielding sheet according to this embodiment further includes a dispersion preparation step of preparing a dispersion containing CNTs (hereinafter also referred to as "CMC") and water. As shown in FIG. 1, the dispersion preparation step includes, for example, a mixture preparation step (step S1) of mixing CNTs, CMC, and water to prepare a mixture, a dispersion step (step S2) of dispersing the CNTs contained in the mixture by an underwater head-on collision method, and an inorganic pigment mixing step (step S3) of mixing an inorganic pigment into the dispersion. Furthermore, the method for producing an electromagnetic wave shielding sheet according to this embodiment includes a drying step (step S4) of drying the dispersion. Each step in the method for producing an electromagnetic wave shielding sheet according to this embodiment will be described in order below.

[0024] 1.1. Mixture preparation process (step S1) 1.1.1. Carbon nanotubes (CNTs) The CNTs used in the mixed solution preparation process include single-walled carbon nanotubes (SWNTs), which are cylindrically wound carbon nanotubes consisting of a single six-membered ring network (graphene sheet), and multi-walled carbon nanotubes (MWNTs), which are concentrically wound carbon nanotubes consisting of multiple graphene sheets. While either SWNTs or MWNTs alone or both may be used in the mixed solution preparation process, it is preferable to use only MWNTs as CNTs, considering the dispersibility of CNTs.

[0025] The CNTs described above are produced to a desired size by, for example, an arc discharge method, a laser ablation method, a CVD (Chemical Vapor Deposition) method, etc. The CNTs used in the mixed solution production step may be produced by any of these methods.

[0026] The diameter of the CNT is not particularly limited, but is preferably 1 nm or more and 100 nm or less, more preferably 5 nm or more and 50 nm or less, and even more preferably 8 nm or more and 15 nm or less. If the diameter of the CNT is within the above range, a dispersion liquid with good dispersibility can be prepared. The diameter of the CNT can be measured using a scanning electron microscope (SEM).

[0027] The fiber length of the CNT is not particularly limited, but is preferably 0.5 μm or more and 50 μm or less, and more preferably 15 μm or more and 35 μm or less. If this is done, a dispersion with good dispersibility can be produced. The fiber length of CNTs can be measured using an SEM. Note that the "fiber length of CNTs" refers to the length of the CNTs when they are bundled together by van der Waals forces, and is the length of the CNTs before they are dispersed in a solvent.

[0028] The BET specific surface area of ​​the CNT is not particularly limited, but is preferably 50 m 2 / g or more 500m 2 / g or less, more preferably 100m 2 / g or more 300m 2 / g or less. If the BET specific surface area of ​​the CNTs is within the above range, a dispersion with good dispersibility can be prepared. Note that the "BET specific surface area" refers to the specific surface area measured by the BET (Brunauer Emmett Teller) method, and can be measured using an automatic specific surface area measuring device.

[0029] The CNT content in the mixture is not particularly limited, but is preferably 0.1% by mass or more and 10.0% by mass or less, more preferably 0.5% by mass or more and 5.0% by mass or less, and even more preferably 1.0% by mass or more and 3.0% by mass or less. If the CNT content is 0.1% by mass or more, an electromagnetic wave shielding sheet with high electromagnetic wave shielding properties (electromagnetic wave shielding properties) can be produced. Furthermore, if the CNT content is 5.0% by mass or less, a dispersion with good dispersibility can be produced.

[0030] 1.1.2. Carboxymethylcellulose sodium (CMC) In the mixed solution preparation process, CMC is used as a dispersant. Here, "dispersant" refers to an additive that disperses CNTs in water and helps prevent the aggregation and sedimentation of CNTs.

[0031] In the mixed solution preparation step, it is preferable to use only CMC as the dispersant. In other words, it is preferable that the mixed solution prepared in the mixed solution preparation step does not contain any additives other than CMC that contribute to preventing the aggregation and sedimentation of CNTs. By using only CMC as the dispersant, it is possible to prevent the inclusion of air bubbles compared to, for example, adding an anionic surfactant or other dispersant in addition to CMC, so the mixed solution can be prepared easily, and an electromagnetic wave shielding sheet without air bubbles can be produced in the drying step described below.

[0032] The weight-average molecular weight of the CMC is not particularly limited, but is preferably 5,000 to 100,000, more preferably 10,000 to 60,000, and even more preferably 10,000 to 35,000. If the weight-average molecular weight of the CMC is 5,000 or more, the CMC easily becomes entangled with the CNTs, improving the dispersibility of the CNTs. However, if the weight-average molecular weight is too large, dispersibility will deteriorate, so the weight-average molecular weight is preferably 100,000 or less. In this specification, the "weight-average molecular weight" refers to the weight-average molecular weight in terms of polystyrene measured by gel permeation chromatography (GPC).

[0033] The degree of etherification of CMC is not particularly limited, but is preferably 0.6 to 1.2, more preferably 0.6 to 0.8. If the degree of etherification of CMC is within the above range, a dispersion liquid with good dispersibility can be prepared.

[0034] In the mixed liquid, the content of CMC is not particularly limited, but is preferably 0.1% by mass or more and 10.0% by mass or less, more preferably 0.5% by mass or more and 5.0% by mass or less, and even more preferably 1.0% by mass or more and 3.0% by mass or less.

[0035] In the mixed solution, the total mass of the CNTs and the inorganic pigment, M SUM Mass M of CMC CMC Ratio of M CMC / M SUM is preferably 1 / 7 or more, more preferably 1 / 6 or more. CMC / M CNT If the ratio is 1 / 7 or more, a dispersion liquid with good dispersibility can be prepared (for details, see "3. Experimental Examples" below).

[0036] In the mixture, the ratio M CMC / M SUM is preferably 3 or less, more preferably 1 or less. CMC / M CNTIf the value is 3 or less, an electromagnetic wave shielding sheet with high electromagnetic wave shielding properties can be manufactured (see "3. Experimental Examples" below for details).

[0037] 1.1.3. Water In the mixed solution preparation process, water is used as a solvent. Examples of water include pure water such as ion-exchanged water, ultrafiltered water, reverse osmosis water, and distilled water, as well as ultrapure water from which ionic impurities have been removed as much as possible. By using water as a solvent, a more environmentally friendly mixed solution can be prepared compared to when an organic solvent is used as a solvent. In the mixed solution preparation process, the mixed solution may be prepared by mixing only CNTs, CMC, and water. In other words, the mixed solution may contain only CNTs, CMC, and water.

[0038] 1.2. Dispersion process (step S2) In the dispersion process, the CNTs contained in the mixed solution are dispersed using the underwater counter-impingement method. By dispersing the CNTs contained in the mixed solution using the underwater counter-impingement method, the CNTs can be dispersed with good dispersibility even if the mixed solution contains only CMC as a dispersant. This makes it possible to produce a dispersion with good dispersibility.

[0039] In the "underwater counter collision method" of this embodiment, a mixed liquid containing CNTs is discharged at high pressure from a pair of nozzle holes (first nozzle hole and second nozzle hole) arranged opposite each other, and the mixed liquid discharged from the first nozzle hole and the mixed liquid discharged from the second nozzle hole are caused to collide with each other to disperse the CNTs. Preferably, in the underwater counter collision method, the CNTs contained in the mixed liquid discharged from the first nozzle hole and the CNTs contained in the mixed liquid discharged from the second nozzle hole are caused to collide with each other to disperse the CNTs. In the underwater counter collision method, as long as the central axes of the first nozzle hole and the second nozzle hole intersect with each other, the two central axes may be on a straight line or may be tilted from each other.

[0040] In the underwater head-on collision method in the dispersion step, the mixed liquid is discharged from a nozzle hole having a diameter of preferably 50 μm to 200 μm, more preferably 80 μm to 120 μm, and even more preferably 100 μm, to cause the mixed liquid to collide with itself. If the nozzle hole diameter is 50 μm or more, even a highly viscous mixed liquid can be discharged from the nozzle hole. Furthermore, if the nozzle hole diameter is 200 μm or less, the collision energy between the mixed liquids can be increased.

[0041] In the underwater head-on collision method in the dispersion step, the mixed liquid is discharged at a pressure of preferably 150 MPa to 250 MPa, more preferably 180 MPa to 220 MPa, and even more preferably 200 MPa, to cause the mixed liquids to collide with each other. If the pressure is 150 MPa or higher, the collision energy between the mixed liquids can be increased. Furthermore, if the pressure is 250 MPa or lower, it is possible to prevent the collision energy from being too high, which would cause the CNT fibers to break and the viscosity of the dispersion to decrease.

[0042] Specifically, the underwater head-on collision method in the dispersion process is performed using a wet atomization device "Starburst Lab" (model name: HJP-25005) manufactured by Sugino Machine Co., Ltd. This wet atomization device has a higher energy density than, for example, an ultrasonic homogenizer or a ball mill, and can produce a dispersion with good dispersibility in a short time. Furthermore, this wet atomization device can minimize the inclusion of impurities, making it possible to produce a dispersion with extremely little inclusion of impurities.

[0043] The number of passes of the mixed solution through the wet atomization device is preferably 1 to 40 times, more preferably 2 to 10 times, and even more preferably 2 or 3 times. If the number of passes is 40 or less, it is possible to prevent the CNT fibers from breaking due to collisions between the mixed liquids, which would result in a decrease in the viscosity of the dispersion. Furthermore, if the number of passes is 2 or more, it is possible to disperse the CNTs with good uniformity. Furthermore, if the number of passes is 2 or more, no significant difference in the shielding ability against electromagnetic waves is confirmed. Therefore, if the number of passes is 2 or more and 10 or less, it is possible to shorten the processing time using the wet atomization device while maintaining dispersibility and electromagnetic wave shielding ability.

[0044] Here, "the number of passes of the mixed liquid in the wet atomization device" refers to the number of times the mixed liquid is circulated in the wet atomization device. For example, "two passes" means that the mixed liquid is circulated twice so that CNTs that have collided once collide again. In this way, the number of passes corresponds to the number of collisions of CNTs contained in the mixed liquid. Furthermore, the number of passes is proportional to the processing time in the wet atomization device. If the processing time in the wet atomization device is long, the number of times the mixed liquid is circulated increases.

[0045] Note that, as long as a dispersion liquid with good dispersibility and an electromagnetic wave shielding sheet with high electromagnetic wave shielding properties can be prepared, the device used in the underwater head-on collision method in the dispersion step is not limited to the above-mentioned wet atomization device "Starburst Lab." Furthermore, as long as a dispersion liquid with good dispersibility and an electromagnetic wave shielding sheet with high electromagnetic wave shielding properties can be prepared, it is not necessary to use the underwater head-on collision method in the dispersion step.

[0046] Furthermore, it is preferable to treat the mixed solution with a homogenizer as a pretreatment before carrying out the dispersion step. The homogenizer may be an ultrasonic type that generates cavitation with ultrasound, an agitation type that agitates the mixed solution, or a pressure type that applies pressure to the mixed solution. Treatment with a homogenizer can reduce CNT agglomerates, making the dispersion step smoother.

[0047] 1.3. Inorganic pigment mixing process (step S3) In the inorganic pigment mixing process, an inorganic pigment is mixed with the dispersion liquid prepared in the dispersion process to prepare a dispersion liquid containing CNTs, inorganic pigment, CMC, and water. The method for mixing the inorganic pigment is not particularly limited, but for example, it is performed using a homogenizer, similar to the pretreatment for the dispersion process. Inorganic pigments are chemically inorganic pigments, and are pigments made from oxides obtained by chemical reactions of natural ores or metals.

[0048] The inorganic pigment particles mixed in the inorganic pigment mixing step have a flat (plate-like) shape, and the aspect ratio of the inorganic pigment is 10 or greater, preferably 50 to 200. Here, the "aspect ratio of the inorganic pigment" refers to the ratio of the particle diameter to the thickness of the inorganic pigment particle. The "particle diameter" refers to the diameter of a circle when viewed in the thickness direction of the particle if the particle is circular, or the diameter of a circle with the same area as the particle if the particle is not circular. The aspect ratio of the inorganic pigment can be determined, for example, by observing 50 inorganic pigment particles using an SEM, measuring the thickness and particle diameter of the inorganic pigment, and calculating the average value. An aspect ratio of an inorganic pigment of 10 or greater can produce an electromagnetic wave shielding sheet with higher electromagnetic wave shielding properties than an inorganic pigment with an aspect ratio of less than 10 (see "3. Experimental Examples" below for details). Inorganic pigments with an aspect ratio of greater than 200 are difficult to obtain.

[0049] The inorganic pigment is preferably at least one selected from the group consisting of kaolin, mica, and talc. When the inorganic pigment is at least one selected from the above group, an electromagnetic shielding sheet with higher electromagnetic shielding properties can be produced compared to when the inorganic pigment is light calcium carbonate or heavy calcium carbonate (see "3. Experimental Examples" below for details). Note that the inorganic pigment may be other than kaolin, mica, or talc as long as the aspect ratio of the inorganic pigment is 10 or more.

[0050] The inorganic pigment is more preferably kaolin. When the inorganic pigment is kaolin, the electromagnetic shielding properties of the electromagnetic shielding sheet tend to be higher than when the inorganic pigment is mica or talc (see "3. Experimental Examples" below for details).

[0051] In the dispersion liquid prepared in the inorganic pigment mixing process, the mass of CNTs M CNT of inorganic pigment M COL Ratio of M COL / M CNT The ratio M is preferably 1 / 4 or more and 1 or less, and more preferably 1 / 4 or more and 1 / 2 or less. COL / M CNT If the ratio M is 1 / 4 or more, the proportion of CNTs is small, so that it is possible to manufacture an electromagnetic wave shielding sheet at low cost. CB / M CNT If the ratio M is 1 or less, an electromagnetic wave shielding sheet with high electromagnetic wave shielding properties can be produced. COL / M CNT If is greater than 1, the proportion of CNT becomes too small, resulting in poor electromagnetic wave shielding properties (see "3. Experimental Examples" below for details).

[0052] By mixing an inorganic pigment in the inorganic pigment mixing step, the viscosity of the dispersion can be increased. This makes it easier to attach the dispersion to a roller when producing an electromagnetic wave shielding sheet. The electromagnetic wave shielding sheet is produced, for example, by using a roll coater to attach the dispersion to a roller, and then using the roller to transfer the dispersion to a substrate such as paper. If the viscosity of the dispersion is low, it becomes difficult to attach the dispersion to the roller. By mixing an inorganic pigment, the viscosity of the dispersion can be increased, making it easier to attach the dispersion to the roller without using a separate thickener.

[0053] If the viscosity of the dispersion is to be further increased, a thickener may be mixed into the dispersion. Examples of thickeners include celluloses such as methyl cellulose and hydroxypropyl cellulose, and their ammonium salts or alkali metal salts; polycarboxylic acids such as poly(meth)acrylic acid and modified poly(meth)acrylic acid, and their alkali metal salts; polyvinyl alcohol (co)polymers such as polyvinyl alcohol, modified polyvinyl alcohol, and ethylene-vinyl alcohol copolymer; saponified copolymers of unsaturated carboxylic acids such as (meth)acrylic acid, maleic acid, and fumaric acid with vinyl esters; and water-soluble polymers such as polyacrylamide copolymers.

[0054] Furthermore, the electromagnetic wave shielding sheet may be produced by a method in which the dispersion is directly applied to the substrate using a coater other than a roll coater, such as a wire bar coater, a knife coater, an air knife coater, a blade coater, a reverse roll coater, or a die coater.

[0055] The viscosity of the dispersion liquid prepared in the inorganic pigment mixing step is not particularly limited, but is preferably 100 mPa·s or more and 3000 mPa·s or less at 20°C. If the viscosity of the dispersion liquid is 100 mPa·s or more, the dispersion liquid can be easily applied to the substrate using a roller as described above. Furthermore, if the viscosity of the dispersion liquid is 3000 mPa·s or less, the mixed liquid can be easily discharged from the nozzle hole of the wet atomization device in the above-mentioned dispersion step. The viscosity of the dispersion liquid can be measured using a viscometer.

[0056] The dispersion liquid prepared in the inorganic pigment mixing step may contain only CNTs, inorganic pigments, CMC, and water, or may contain additives in addition to CNTs, inorganic pigments, CMC, and water, such as preservatives and pH adjusters.

[0057] The total mass of the CNTs and the inorganic pigment contained in the dispersion liquid prepared in the inorganic pigment mixing step, M SUM Mass M of CMC CMC Ratio of MCMC / M SUM is the ratio M CMC / M SUM is the same as

[0058] 1.4. Drying process (step S4) In the drying step, the dispersion liquid prepared in the inorganic pigment mixing step is dried. This allows the water content of the dispersion liquid to evaporate, thereby producing an electromagnetic wave shielding sheet. The method for drying the dispersion liquid is not particularly limited, and drying may be performed using a hot plate or heater, or natural drying may be used.

[0059] In the drying step, the dispersion may be placed in a petri dish or the like and then dried to produce an electromagnetic wave shielding sheet.

[0060] Alternatively, in the drying step, the dispersion may be applied to a substrate such as paper, and the applied dispersion may be dried to produce an electromagnetic wave shielding sheet. The method for applying the dispersion to the substrate is not particularly limited, and examples include a method in which the dispersion is applied directly to the substrate using a wire bar coater, knife coater, air coater, blade coater, reverse roll coater, die coater, or the like, and a method in which the dispersion is applied to a roller and the dispersion applied to the roller is transferred to the substrate, such as a so-called roll coater.

[0061] 1.5. Variations In the above, an example has been described in which the dispersion preparation process for preparing a dispersion includes a mixed solution preparation process (step S1) of mixing CNTs, CMC, and water to prepare a mixed solution, a dispersion process (step S2) of dispersing the CNTs contained in the mixed solution by an underwater head-on collision method, and an inorganic pigment mixing process (step S3) of mixing an inorganic pigment into the dispersion prepared in the dispersion process, but the dispersion preparation process is not limited to this example.

[0062] In the dispersion preparation step, for example, CNTs, an inorganic pigment, CMC, and water may be mixed to prepare a mixed liquid, and the mixed liquid may be subjected to an underwater head-on collision method to disperse the CNTs. Alternatively, in the dispersion preparation step, for example, an inorganic pigment powder and a CMC powder may be added to a CNT-containing liquid that has been subjected to the underwater head-on collision method, and then mixed to prepare a dispersion in which CNTs are dispersed. However, if the underwater head-on collision method is performed on a liquid containing an inorganic pigment, the aspect ratio of the inorganic pigment may become less than 10 due to the collisions in the underwater head-on collision method. Therefore, it is preferable to perform the underwater head-on collision method on a mixed liquid before mixing the inorganic pigment.

[0063] 2. Electromagnetic wave shielding sheet Next, an electromagnetic wave shielding sheet according to this embodiment will be described. The electromagnetic wave shielding sheet according to this embodiment is an electromagnetic wave shielding sheet manufactured by the above-mentioned "1. Manufacturing method of electromagnetic wave shielding sheet." Therefore, the electromagnetic wave shielding sheet according to this embodiment contains CNT, an inorganic pigment, and CMC, and the aspect ratio of the inorganic pigment is 10 or more. The electromagnetic wave shielding sheet according to this embodiment may be composed of CNT, an inorganic pigment, and CMC.

[0064] The ratio of the inorganic pigment to the mass of the CNTs contained in the electromagnetic wave shielding sheet according to this embodiment is the same as the ratio of the inorganic pigment to the mass of the CNTs contained in the dispersion liquid prepared in the inorganic pigment mixing step. SUM Mass M of CMC CMC Ratio of M CMC / M SUM is the ratio M in the dispersion liquid prepared in the inorganic pigment mixing process CMC / M SUM The mass ratio of the components of such an electromagnetic wave shielding sheet can be measured by mass spectrometry.

[0065] The electromagnetic wave shielding sheet according to this embodiment has a shape in which the size in the direction perpendicular to the thickness direction is sufficiently large relative to the thickness. The shape is not particularly limited, but may be, for example, a circle, an ellipse, a rectangle, or other polygon.

[0066] The thickness of the electromagnetic wave shielding sheet according to this embodiment is not particularly limited, but is preferably 0.1 μm or more and 500 μm or less, and more preferably 1 μm or more and 300 μm or less. The thickness of the electromagnetic wave shielding sheet can be measured using an SEM. If the thickness of the electromagnetic wave shielding sheet is 0.1 μm or more, the electromagnetic wave shielding properties of the electromagnetic wave shielding sheet can be improved. Furthermore, if the thickness of the electromagnetic wave shielding sheet is 500 μm or less, the occurrence of cracks in the electromagnetic wave shielding sheet can be suppressed.

[0067] The electromagnetic wave shielding sheet according to this embodiment has high shielding properties for frequencies of, for example, 10 MHz to 100 GHz, although this is not particularly limited. The shielding properties of the electromagnetic wave shielding sheet are evaluated by, for example, the coaxial tube method, the free space method, the microstrip line method, the KEC (Kansai Electronics Industry Development Center) method, etc.

[0068] 3. Experimental Example The present invention will be explained in more detail below by way of experimental examples, but the present invention is not limited to these examples.

[0069] 3.1. First experimental example 3.1.1. Fabrication of electromagnetic wave shielding sheet First, a mixture was prepared by mixing CNT, CMC, and water. A homogenizer called "Biomixer BM-2" manufactured by Nippon Seiki Seisakusho Co., Ltd. was used for mixing. The mixing time was 5 minutes.

[0070] The CNTs used were "K-Nanos-100P" manufactured by Kumho Petrochemical Co., Ltd. The CNTs were MWNTs, with a diameter of 8 nm to 15 nm, a fiber length of 27 μm (bundle), and a BET specific surface area of ​​220 m 2 / g.

[0071] The CMC used was "Cellogen 5A" manufactured by Daiichi Kogyo Seiyaku Co., Ltd. The CMC had a weight average molecular weight of 11,000 to 15,000 and a degree of etherification of 0.7. Only CMC was used as the dispersant. No additives such as thickeners were added.

[0072] Next, the mixed solution was subjected to underwater head-on collision. The underwater head-on collision was performed using a wet atomization device "Starburst Lab" (model name: HJP-25005) manufactured by Sugino Machine Co., Ltd. The diameter of the nozzle hole from which the mixed solution was discharged was set to 100 μm, and the discharge pressure of the mixed solution was set to 200 MPa. The mixed solution was passed through the wet atomization device two times. In this way, a dispersion containing CNT, CMC, and water was produced.

[0073] Next, an inorganic pigment was added to the dispersion and mixed to produce a dispersion containing the inorganic pigment. This produced a dispersion containing CNTs, inorganic pigment, CMC, and water. A homogenizer called "Biomixer BM-2" manufactured by Nippon Seiki Seisakusho Co., Ltd. was used for mixing. The mixing time was 5 minutes.

[0074] The dispersion containing the inorganic pigment was prepared so that the ratio of CMC to the total mass of CNT and inorganic pigment was 1 ((CNT + inorganic pigment): CMC = 1:1). The dispersion was also prepared so that the total content of CNT, inorganic pigment, and CMC was 5 mass%.

[0075] In this experimental example, eight types of inorganic pigments were used. Figure 2 is a table explaining the inorganic pigments used in this experimental example. In Figure 2 and below, light calcium carbonate is referred to as "light calcium carbonate." Heavy calcium carbonate is called "heavy calcium carbonate."

[0076] The mass ratio of the inorganic pigment to the mass of the CNT was varied from 1 / 4 to 4 (CNT:inorganic pigment=4:1 to 1:4).

[0077] The dispersion liquid was applied to paper ("Mu Coat Neos" (registered trademark) manufactured by Hokuetsu Corporation, basis weight 157 g / m) by a roll coater. 2 ) and then dried overnight at 50°C to evaporate the water, producing coated paper.

[0078] In this manner, a coated paper was prepared as an electromagnetic wave shielding sheet.

[0079] Furthermore, coated paper containing no inorganic pigment was prepared by increasing the CNT content to compensate for the absence of inorganic pigment, so that the total content of CNT and CMC in the dispersion was 5 mass%.

[0080] 3.1.2. Evaluation of the electromagnetic wave shielding properties of coated paper (1) Evaluation method The electromagnetic wave shielding properties of coated paper were evaluated by measuring "S21" using the coaxial tube method. "S21" corresponds to transmission loss, and the larger the absolute value of "S21", the higher the electromagnetic wave shielding properties. The test equipment used was the network analyzer "ZVA67" manufactured by ROHDE & SCHWARZ and the shielding effectiveness measurement kit "S-39D" manufactured by KEYCOM. The measurement frequencies were 45MHz to 18GHz.

[0081] (2) Evaluation results Figure 3 is a table showing the evaluation results of the electromagnetic wave shielding properties of coated papers. Figure 3 shows "S21" at frequencies of 300 MHz and 7 GHz. In Figure 3 and the following description, "Contour 1500" in Figure 2 is referred to as "Kaolin 1," "Hydrogloss 90" as "Kaolin 2," "Brilliant-15" as "Light Kaolin 1," "Tama Pearl TP121" as "Light Kaolin 2," "Softon 1500" as "Heavy Kaolin 1," and "Softon 2200" as "Heavy Kaolin 2." Also, in Figure 3 and the following description, coated paper containing CNTs but no inorganic pigments is referred to as "CNT only."

[0082] The thickness of the coated paper is shown in Figure 3. The thickness was measured using an SEM. In Figure 3, "thickness" indicates the total thickness of the coated paper minus the thickness of the base paper.

[0083] As shown in Figure 3, kaolin 1,2, mica, and talc, which have inorganic pigment aspect ratios of 10 or more, had larger absolute values ​​of "S21" than light kaolin 1,2 and heavy kaolin 1,2, which have inorganic pigment aspect ratios of less than 10.

[0084] Therefore, it was found that if the aspect ratio of the inorganic pigment is 10 or more, it is possible to produce an electromagnetic shield with higher electromagnetic wave shielding properties than when the aspect ratio of the inorganic pigment is less than 10. In particular, kaolins 1 and 2 tended to have larger absolute values ​​of "S21" than mica and talc. Furthermore, kaolin 1, which has an aspect ratio of 50 or more, tended to have a larger absolute value of "S21" than other inorganic pigments.

[0085] Furthermore, as shown in Figure 3, the absolute value of "S21" decreased as the ratio of the mass of inorganic pigment to the mass of CNT increased. In particular, when the ratio was 4 (CNT:inorganic pigment = 1:4), the absolute value of "S21" was less than 5 dB at both the measurement frequencies of 300 MHz and 7 GHz, and the electromagnetic wave shielding properties were poor. On the other hand, when the ratio was 1 (CNT:inorganic pigment In the case of a CNT:inorganic pigment ratio of 1:1 or 4 (CNT:inorganic pigment ratio of 4:1), the absolute value of "S21" was greater than 10 dB at both the measurement frequencies of 300 MHz and 7 GHz, demonstrating high electromagnetic wave shielding properties.

[0086] Therefore, it was found that by setting the ratio of the mass of inorganic pigment to the mass of CNT to between 1 / 4 and 1, a significant decrease in electromagnetic wave shielding properties can be prevented even if part of the CNT is replaced with inorganic pigment.

[0087] 3.1.3. Evaluation of the electromagnetic wave shielding properties of dried films The dispersion prepared in "3.1.1. Preparation of electromagnetic wave shielding sheet" above was placed in a petri dish without being coated on paper, and dried overnight at 50°C to evaporate the water, producing a dry film as an electromagnetic wave shielding sheet. In other words, the dry film is in a state where it has not been coated on a substrate such as paper.

[0088] The electromagnetic wave shielding properties of the dried film were evaluated in the same manner as for the coated paper. Figure 4 is a table showing the evaluation results of the electromagnetic wave shielding properties of the dried film. Figure 4 shows "S21" at frequencies of 300 MHz and 7 GHz. As shown in Figure 4, the dried film was thicker than the coated paper, and therefore had better electromagnetic wave shielding properties than the coated paper. Other than this, the behavior was similar to that of the coated paper.

[0089] 3.1.4. Evaluation of dry film formability The film-forming properties of the above-mentioned dried film were evaluated according to the following specific evaluation criteria:

[0090] A: No cracks or waviness occurred. B: No cracks occurred, but waviness occurred. C: Cracks occurred.

[0091] The term "wavy" refers to a state in which the film undulates like waves, but does not result in cracks.

[0092] Figure 4 shows the evaluation results of the film-forming properties of the dried films. As shown in Figure 4, kaolin 1,2, mica, and talc, which have inorganic pigment aspect ratios of 10 or more, had better film-forming properties than light kaolin 1,2 and heavy kaolin 1,2, which have inorganic pigment aspect ratios of less than 10. Kaolin 1,2, mica, and talc have small specific surface areas due to their high aspect ratios. Therefore, it is presumed that the inorganic pigments were less likely to aggregate when the dispersion was dried, and cracks and waviness did not occur.

[0093] Furthermore, as shown in FIG. 4, the film-forming properties tended to deteriorate as the ratio of the mass of the inorganic pigment to the mass of the CNT increased.

[0094] This evaluation revealed that there is a correlation between electromagnetic wave shielding properties and film-forming properties, and that the better the film-forming properties, the higher the electromagnetic wave shielding properties tend to be.

[0095] 3.2. Second experimental example In the first experimental example described above, a dispersion containing an inorganic pigment was prepared, whereas in the second experimental example, a dispersion containing only CNT, CMC, and water was prepared without using an inorganic pigment, and the dispersibility and electromagnetic wave shielding properties were evaluated.

[0096] Both the CNT and the inorganic pigment are inorganic materials, and the evaluation results of the second experimental example were obtained by examining the dispersibility of a dispersion containing CNT, an inorganic pigment, CMC, and water, and the properties of a material produced from the dispersion. The evaluation of dispersibility and electromagnetic wave shielding property will be explained below in order.

[0097] 3.2.1. Evaluation of CNT dispersibility (1) Preparation of dispersion A mixture was prepared by mixing only CNT, CMC, and water. The total content of CNT and CMC in the mixture was 5% by mass. The mass ratio of CMC to CNT was varied from 1:9 to 9 (CNT:CMC = 1:9 to 9:1).

[0098] Except for the above, dispersions 1 to 10 were prepared in the same manner as in "3.1.1. Preparation of electromagnetic wave shielding sheet" above.

[0099] Dispersion 11 was prepared in the same manner as Dispersion 1 described above, except that CMC was not mixed in when preparing the mixture.

[0100] Except for not performing the underwater head-on collision method on the mixed liquid, dispersion 12 was prepared in the same manner as dispersion 4. Fig. 5 is a table showing the preparation conditions for dispersions 1 to 12.

[0101] (2) Evaluation method Dispersions 1 to 12 prepared as described above were placed in a Petri dish with a diameter of 8.5 cm and dried overnight at 50°C to evaporate the water. The film-forming properties of the dried material were then observed to evaluate the dispersibility of the CNTs. The better the dispersibility of the CNTs, the more uniform the film formed. The specific evaluation criteria are as follows:

[0102] A: A crack-free film was formed over the entire surface of the petri dish. B: A film was formed over the entire surface of the petri dish, but cracks occurred. C: No film formed.

[0103] (3) Evaluation results Figure 5 shows the evaluation results of the dispersibility of Dispersions 1 to 12. Figure 6 is a photograph showing the state of Dispersions 1 to 12 after they were placed in a petri dish and dried at 50°C overnight.

[0104] As shown in FIGS. 5 and 6, Dispersions 1 to 8 had better film-forming properties and better CNT dispersibility than Dispersions 9 to 12.

[0105] No significant difference in film-forming properties was observed among Dispersions 1 to 7, and crack-free films were formed. Dispersion 8 had a low CMC content relative to the CNTs, causing cracks in the film. Dispersions 9 and 10 had too low a CMC content relative to the CNTs, preventing film formation. This evaluation revealed that dispersions with good dispersibility can be prepared by setting the ratio of CMC mass to CNT mass to 1 / 7 or more, preferably 1 / 6 or more.

[0106] Dispersion 11 did not contain CMC in the mixed solution, and therefore the dispersibility of the CNTs was poor, and like Dispersions 9 and 10, no film was formed.

[0107] For Dispersion 12, the mixed liquid was not subjected to the underwater head-on collision method, so the CNTs had poor dispersibility and no film was formed. It was found that a dispersion with good dispersibility can be produced by dispersing CNTs using the underwater head-on collision method.

[0108] 3.2.2. Evaluation of electromagnetic wave shielding (1) Evaluation results when changing the ratio of CNT to CMC Coated papers were prepared from the above dispersions 1 to 12 in the same manner as described above in "3.1.1. Preparation of electromagnetic wave shielding sheet." The electromagnetic wave shielding properties were then evaluated in the same manner as described above in "3.1.2. Evaluation of the electromagnetic wave shielding properties of coated paper."

[0109] Figure 7 is a table showing the evaluation results of the electromagnetic wave shielding properties of coated paper. Figures 8 and 9 are graphs showing "S21" versus frequency, and the "S21" values ​​shown in Figure 7 are extracted from Figures 8 and 9 for 300 MHz and 7 GHz.

[0110] 8 and 9 are graphs showing "S21" of coated paper, the measurement frequencies in FIG. 8 being 45 MHz to 3 GHz, and the measurement frequencies in FIG. 9 being 500 MHz to 18 GHz.

[0111] As shown in Figures 7 to 9, for coated papers made from Dispersions 1 to 4, the absolute value of "S21" increased as the CNT content increased. For coated papers made from Dispersions 4 to 7, "S21" remained roughly constant. For coated papers made from Dispersions 8 to 10, the absolute value of "S21" was smaller than for coated papers made from Dispersions 4 to 7. This is thought to be because Dispersions 8 to 10 have poor dispersibility, as described above, and therefore have poor electromagnetic wave shielding properties.

[0112] This evaluation revealed that electromagnetic wave shielding properties can be improved by setting the ratio of the mass of CMC to the mass of CNT to 1 / 6 or more and 3 or less (CNT:CMC = 1:3 to 6:1), preferably 1 / 6 or more and 1 or less (CNT:CMC = 1:1 to 6:1).

[0113] (2) Evaluation results when the number of passes is changed For the above-mentioned Dispersion 4 (CNT:CMC = 1:1), the number of passes was varied by changing the treatment time of the mixed solution in the wet atomizer, and coated paper was produced in the same manner as in "(1) Evaluation when the CNT to CMC ratio was changed." The electromagnetic shielding properties of the coated paper were then evaluated. The amount of the mixed solution was adjusted so that a treatment time of 0.5 minutes in the wet atomizer was equivalent to one pass. Furthermore, coated paper was produced from the above-mentioned Dispersion 12 (a dispersion not treated with the wet atomizer) and evaluated in the same manner. Because coated paper allows for a thinner CNT-containing sheet than a dry film, it was possible to evaluate even Dispersion 12 with poor dispersibility.

[0114] Fig. 10 is a table showing the evaluation results of the electromagnetic wave shielding property when the number of passes was changed. Figs. 11 and 12 are graphs showing "S21" versus frequency, and the "S21" shown in Fig. 10 is the value extracted at 300 MHz and 7 GHz from Figs. 11 and 12, respectively. The measurement frequencies in Fig. 11 were 45 MHz to 3 GHz, and the measurement frequencies in Fig. 12 were 500 MHz to 18 GHz.

[0115] As shown in Figures 10 to 12, the coated paper that had been treated with a wet atomization device had higher electromagnetic wave shielding properties than the untreated coated paper. As shown in Figure 10, the untreated coated paper had poor electromagnetic wave shielding properties despite its large thickness.

[0116] This evaluation revealed that treatment with a wet atomization device, i.e., the underwater head-on collision method, can improve the shielding properties. Note that, in Figures 10 to 12, no significant difference in the electromagnetic wave shielding properties was confirmed for coated paper treated with a wet atomization device.

[0117] The above-described embodiment and modifications are merely examples, and the present invention is not limited to these. For example, the embodiments and modifications can be combined as appropriate.

[0118] The present invention is not limited to the above-described embodiments, and various modifications are possible. For example, the present invention includes configurations that are substantially identical to the configurations described in the embodiments. A substantially identical configuration means, for example, a configuration that has the same function, method, and result, or a configuration that has the same purpose and effect. The present invention also includes configurations in which non-essential parts of the configurations described in the embodiments are replaced. The present invention also includes configurations that achieve the same effects or purposes as the configurations described in the embodiments. The present invention also includes configurations in which publicly known technology is added to the configurations described in the embodiments.

Claims

1. A step of preparing a dispersion liquid containing carbon nanotubes, an inorganic pigment, sodium carboxymethylcellulose, and water; drying the dispersion; Including, The aspect ratio of the inorganic pigment is 14 or more; a ratio of the mass of the sodium carboxymethylcellulose to the total mass of the carbon nanotubes and the inorganic pigment in the dispersion is 3 or less.

2. The method for producing an electromagnetic wave shielding sheet according to claim 1 , wherein the inorganic pigment is at least one selected from the group consisting of kaolin, mica, and talc.

3. The method for producing an electromagnetic wave shielding sheet according to claim 1 , wherein the inorganic pigment is kaolin.

4. The method for producing an electromagnetic wave shielding sheet according to claim 1 , wherein in the dispersion liquid, a ratio of a mass of the inorganic pigment to a mass of the carbon nanotubes is ¼ or more and 1 or less.

5. The method for producing an electromagnetic wave shielding sheet according to claim 1 , wherein in the step of preparing the dispersion, only the sodium carboxymethyl cellulose is used as a dispersant.

6. The step of preparing the dispersion liquid includes: mixing the carbon nanotubes, the sodium carboxymethylcellulose, and the water to prepare a mixed solution; The carbon nanotubes contained in the mixture are dispersed by an underwater head-on collision method. and a step of dispersing the carbon nanotubes contained in the mixed liquid and then mixing the inorganic pigment; A method for producing the electromagnetic wave shielding sheet according to claim 1 , comprising:

7. The method for producing an electromagnetic wave shielding sheet according to claim 1 , wherein the inorganic pigment has an aspect ratio of 20 or more.

8. Carbon nanotubes, an inorganic pigment, and sodium carboxymethylcellulose, The aspect ratio of the inorganic pigment is 14 or more; An electromagnetic wave shielding sheet, wherein a ratio of the mass of the sodium carboxymethylcellulose to the total mass of the carbon nanotubes and the inorganic pigment is 3 or less.

9. 9. The electromagnetic wave shielding sheet according to claim 8, wherein the inorganic pigment is at least one selected from the group consisting of kaolin, mica, and talc.

10. The electromagnetic wave shielding sheet according to claim 8 or 9, wherein the inorganic pigment is kaolin.

11. 11. The electromagnetic wave shielding sheet according to claim 8, wherein a ratio of a mass of the inorganic pigment to a mass of the carbon nanotubes is 1 / 4 or more and 1 or less.

12. 12. The electromagnetic wave shielding sheet according to claim 8, wherein the inorganic pigment has an aspect ratio of 20 or more.

Citation Information

Patent Citations

  • High elastic aqueous conductive nano coating

    CN101353547A

  • Coating composition and its manufacturing method, and resin molding and its manufacturing method

    JP2007031710A

  • Inkjet recording medium, and method for producing the same

    JP2012076319A

  • Carbon nanotube aqueous dispersion and composite sheet obtained by using the same

    JP2013082610A

  • Fine carbon fiber-containing aqueous polyurethane resin solution and conductive film using the same

    JP2015120837A